Higher Education in an Era of Digital Competition: Emerging Organizational Models - Hanna, Donald E. (Online Learning, 1998)
Growing demand among learners for improved accessibility and convenience, lower costs, and direct application of content to work settings is radically changing the environment for higher education in the United States and globally. In this rapidly changing environment, which is increasingly based within the context of a global, knowledge-based economy, traditional universities are attempting to adapt purposes, structures, and programs, and new organizations are emerging in response. Organizational changes and new developments are being fueled by accelerating advances in digital communications and learning technologies that are sweeping the world. Growing demand for learning combined with these technical advances is in fact a critical pressure point for challenging the dominant assumptions and characteristics of existing traditionally organized universities in the 21st century. This combination of demand, costs, application of content and new technologies is opening the door to emerging competitors and new organizations that will compete directly with traditional universities and with each other for students and learners. This paper describes and analyzes seven models of higher education organization that are challenging the future preeminence of the traditional model of residential higher education. These models are emerging to meet the new conditions and to take advantage of the new environment that has created both opportunity and risk for all organizations, and which demands experimentation of structure, form, and process. Each of the seven models discussed offers an alternative to traditional residential higher education. Several models are in their infancy. Several others operate at the margin of organizations with other core businesses or priorities. At least one of the models depends upon extensive collaborations. All of the models incorporate features that are designed to enable universities to better respond to new educational demands and opportunities at a national and international level. Taken together, these organizational models are emerging as significant forces in providing education and training, and as powerful competitors to traditional universities. They offer the prospect of rapidly changing where, when, how and for what purpose education is organized within both the corporate and the higher education communities in the United States and throughout the world. The result is a dynamic competitive environment among traditional universities that are adapting learning processes and administrative procedures, alternative nontraditional universities that are adapting technologies to better serve their existing primarily adult constituencies, and new universities that are being formed around the promise of virtual environments. The thesis of this paper is that growth in worldwide demand for learning is combining with improved learning technologies to force existing universities to rethink their basic assumptions and marketing strategies. This new digital environment is further encouraging and enabling the creation of new and innovative organizational models of that are challenging traditional residential universities to change more quickly and dynamically.